Analisis Kepemimpinan Daud dalam 1 Samuel 23:1-13 berdasarkan Teori Kepemimpinan Spiritual dari Louis William Fry - Yose Yose; Panca Parulian S. (EDULEAD: Journal of Christian Education and Leadership, 2023)
The starting point of the author's thoughts to elaborate  spiritual leadership with theological foundations is the discovery of phenomena both in general and in the church related to leadership deviations. To achieve this, this study uses a narrative hermeneutic approach, and the results of the analysis are viewed using the perspective of Fry's theory of spiritual leadership. The results of the analysis are (1) Spiritual leadership that Fry has described with elements of Vision, Faith/Hope and Altruistic Love can also be seen in David's leadership in the text of 1 Samuel 23:1-13; (2) David's leadership can be used as a good example in leadership in general and also in Christian leadership in transformation efforts by relying on God and putting the vision on Faith/Hope to God, seeking God before making a decision to act; and (3) the success of the vision in David's leadership was not the achievement of his personal goals and the goals of his followers, but the achievement of God's purposes; and (4) The application of Altruistic Love in leadership will be able to bring change in a much better directionAbstrakTitik pangkal pemikiran penulis dalam membangun kepemimpinan spiritual dengan fondasi teologis adalah ditemukannya fenomena-fenomena baik umum dan gereja terkait penyelewengan kepemimpinan. Untuk mencapai itu, penelitian ini menggunakan pendekatan hermeneutika naratif dan hasil dari analisis tersebut dilihat menggunakan perspektif teori kepemimpinan spiritual dari Louis W. Fry. Hasil dari analisis tersebut adalah (1) Kepemimpinan spiritual yang telah dijelaskan Fry dengan elemen Visi, Iman/Harapan dan Cinta Altruistis dapat terlihat juga dalam kepemimpinan Daud dalam teks 1 Samuel 23:1-13; (2) Kepemimpinan Daud dapat dijadikan teladan baik dalam kepemimpinan secara umum dan juga di dalam kepemimpinan Kristen dalam upaya transformasi dengan bergantung kepada Tuhan dan meletakan visi pada Iman/Harapan kepada Tuhan, mencari Tuhan sebelum mengambil keputusan untuk bertindak; dan (3) Keberhasilan visi di dalam kepemimpinan Daud bukanlah tercapainya tujuan pribadinya dan tujuan pengikutnya, melainkan tercapainya tujuan Tuhan; dan (4) Penerapan Cinta Altruistis dalam kepemimpinan akan mampu membawa perubahan ke arah yang jauh lebih baik.